2017
DOI: 10.1007/s00277-017-3137-0
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of response to erythropoietin stimulating agents in myelodysplastic syndrome: from the Canadian MDS patient registry

Abstract: Prediction of response to erythropoietin stimulating agents (ESAs) in anemic MDS patients is often based on the Nordic score. We wished to validate the Nordic score (IWG 2006 response criteria) in a larger cohort and determine if other variables such as IPSS/IPSS-R, ferritin, LDH, and a novel European ESA response score (Santini 2013) were of prognostic importance. We analyzed 208 ESA-treated MDS patients (WHO 2008 criteria) from a prospective registry. Ninety-four and 93% had lower risk scores by IPSS (low/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
1
17
0
2
Order By: Relevance
“…Notably, when the strict interpretation of these criteria was relaxed, the observed response rate in the studies increased from 15% to 24% in ARCADE (Platzbecker et al , ) and from 32% to 46% in EPOANE3021 (Fenaux et al , ). Similar support for the use of other criteria for measuring erythroid response has been provided from other ESA studies (Buckstein et al , ; Houston et al , ).…”
Section: Discussionsupporting
confidence: 64%
“…Notably, when the strict interpretation of these criteria was relaxed, the observed response rate in the studies increased from 15% to 24% in ARCADE (Platzbecker et al , ) and from 32% to 46% in EPOANE3021 (Fenaux et al , ). Similar support for the use of other criteria for measuring erythroid response has been provided from other ESA studies (Buckstein et al , ; Houston et al , ).…”
Section: Discussionsupporting
confidence: 64%
“…Based on the most influential predictive factors discussed above, various groups have proposed scoring systems to predict hematologic response to ESAs with or without G-CSF among patients with MDS (Table 2) [39,56,60,61]. These all include sEPO levels, although the cutoffs and scores vary between systems.…”
Section: Scoring Systems Predictive Of Hematologic Response To Esas Amentioning
confidence: 99%
“…The earliest system additionally included only transfusion need [39]. Later systems [56,60,61] included either IPSS-R or IPSS risk levels. Response rates for the most favorable scores are 74-85%, falling to 7-23% for the least favorable scores ( Table 2).…”
Section: Scoring Systems Predictive Of Hematologic Response To Esas Amentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary results showed that the poor outcome of severe reduced ARC could not be reversed by the immunosuppressive or hypo-methylating agents. Also, lower ARC was significantly associated with higher EPO level, which was considered as a biomarker for poor erythroid response to erythropoiesis stimulating agents 41 Given that the severe ineffective erythropoiesis did not affect survival after HSCT, early HSCT should be suitable therapy for these patients.…”
Section: Discussionmentioning
confidence: 99%